The Digital Inheritance - Vidić Trninić, Jelena; Kovacevic, Milica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Nowadays, the life of an individual can hardly be imagined without using the attainment of the IT system. Its vertiginous development and people's familiarity with it has led to the fact that personal data are becoming an important, if not the most important, resource today. So much so, that they are also called "the oil of new era". This is coming from the fact that companies now charge users for their mostly free services by asking them for more and more different data in return. Contrary to that, most of the users do not think about what will happen to their personal data after their death or are not aware of all the ways they can dispose of their digital assets mortis causa. The authors consider the question of heritability of digital goods, and especially the possibility of disposing of them in the event of the death of the testator. Analyzing the current domestic regulations, as well as the direction of development of digital inheritance in other European countries, at the same time the authors are trying to find an answer to the question how to understood the term of digital inheritance within the framework of our country.
Keywords: digitized data, digital assets, inheritance, universal succession, last will